INSPIRASI QUR’ANI; PARADIGMA HUBUNGAN ANTAR AGAMA - Achmad Lutfi (Diya Al-Afkar: Jurnal Studi al-Quran dan al-Hadis, 2018)
The phenomenon of religious plurality has become a social fact that must be faced by modern society. Such a phenomenon for people who are not accustomed to and do not have experience in peaceful coexistence will certainly cause their own problems, forcing experts from various disciplines to formulate a solution or approach in response to these problems. This is mainly because the main function of religion actually lies in the answer to humanitarian problems. Harmonious relations between religious people are an urgent goal to be realized. So it is very important to find a meeting point so that we can live together in peace and harmony with each other. The Qur'an has signaled to mankind about inter-religious meeting points. In the Al-Qur'an there are verses that emphasize the principle of religious pluralism.